BMI Effect on Academic Performance of School-Going Students in Jhajjar, Haryana – A Correlational Study - Shastri, Aruna; Kusum,; Rajaman, Sathish (Indian Journal of Nursing Sciences, 2024)
The present study was selected with the aim to assess body mass index (BMI) and academic performance among school-going children and to find correlation between them. A non-experimental correlational study was conducted among school-going adolescents of 6th–10th class in three different private schools of district Jhajjar. Non-probability convenient sampling technique was adopted for the study. The sample size was 430. Data were collected using survey method. Descriptive and inferential statistics were used to analyze the data with the help of SPSS. Among all study samples 131 had BMI <16 (very severely underweight), 66 had BMI 16.0–16.9 (severely underweight), 67 had BMI 17–18.4 (Underweight), and 166 had normal BMI (18.5–24.9). The mean, median, and standard deviation of BMI were 17.72, 17.3, and 2.8, respectively. Forty-five students had excellent performance (>90%), 208 had good performance (>75–90), 128 had average performance (>60–75%), 46 had below average performance (>45–60%), and three had poor academic performance (<45%). The mean, median, and standard deviation score of academic performance were 59, 70, 60, and 9.5, respectively. A significant positive correlation (r = 0.142) was found between BMI and academic performance at P < 0.05. The study concluded that majority of the students had normal BMI and maximum had good academic performance which showed that if the child is healthy and having normal BMI; then, academic performance can be better.